2019
DOI: 10.1097/qad.0000000000002075
|View full text |Cite
|
Sign up to set email alerts
|

HIV latency can be established in proliferating and nonproliferating resting CD4+ T cells in vitro

Abstract: OBJECTIVE:To determine whether latency can be established and reversed in both proliferating and non-proliferating CD4 + T cells in the same model in vitro.METHODS: Activated CD4 + T cells were infected with either a non-replication competent, luciferase reporter virus or wild-type full-length enhanced green fluorescent protein (EGFP) reporter virus and cultured for 12 days. The cells were then sorted by flow cytometry to obtain two distinct T cell populations that did not express the T cell activation markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…However, proliferation alone is not effective at inducing HIV expression. Moso et al recently demonstrated HIV latency is effectively maintained in proliferating cells [97]. Interestingly, Vandergeeten et al also showed that the γ-chain cytokine IL-7 does not induce HIV latency reversal in latently infected cells, but can support enhanced HIV expression when the cells are productively infected [74].…”
Section: Discussionmentioning
confidence: 99%
“…However, proliferation alone is not effective at inducing HIV expression. Moso et al recently demonstrated HIV latency is effectively maintained in proliferating cells [97]. Interestingly, Vandergeeten et al also showed that the γ-chain cytokine IL-7 does not induce HIV latency reversal in latently infected cells, but can support enhanced HIV expression when the cells are productively infected [74].…”
Section: Discussionmentioning
confidence: 99%
“…Research during the past twenty-five years has made considerable advances in understanding the mechanisms of latency establishment [ 9 ]. The importance of the cell state at the time of reservoir establishment has become more and more appreciated for potential curative interventions [ 10 , 11 ]. However, the preferential state of cells which facilitates establishment of latency is still not fully delineated.…”
Section: Introductionmentioning
confidence: 99%
“…Primary CD4 + T cell models are especially useful and easily established using cells from HIV negative donors. A widely used model for HIV latency involves selection of resting CD4 + T cells (negative for expression of T cell activation markers CD69, HLADR, CD25) that have been stimulated with CCR7 ligands to support viral integration with limited viral replication (24,(26)(27)(28). Primary cell models use in vitro infection with HIV viruses of varying subtypes (e.g.…”
Section: Introductionmentioning
confidence: 99%